Brand Trust, Awareness, dan Loyalty sebagai Penggerak Brand Equity pada Pasar Smartphone - Adisti, Lintang Shafa; Nurlaela, Siti (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Fierce competition in the smartphone industry requires companies to strengthen brand equity to maintain competitiveness and build long-term relationships with consumers. This study aims to analyze brand awareness, brand image, perceived quality, brand association, brand loyalty, and brand trust on brand equity in the smartphone industry. A quantitative approach was used in this study with multiple linear regression analysis techniques taken based on data from 111 respondents. The results of this study show that brand awareness, brand loyalty, and brand trust have a positive influence on brand equity, while brand image, brand association, and perceived quality do not have a significant influence. These findings confirm the importance of brand trust, brand awareness, and brand loyalty as factors that can strengthen brand equity. Therefore, companies are advised to focus on increasing consumer trust, maintaining consumer loyalty, and strengthening sustainable promotions or advertising to maintain competitiveness in the smartphone market.